Implementation of the Philosophical Concept of Student Centred Education at Senior Secondary Level - Dahanayake, S.S. (My University, 2006)
Various reports on Education both locally and globally have emphasized the need to improve quality of Education. In order to achieve quality education in Sri Lanka, in 1997 reforms introduced new policies. Particularly they recommended that education should be Student Centred not Teacher Centred. Secondary education plays a crucial role in nurturing and providing future citizens of a country. The purpose of this research is to find out how Student Centred Education is being implemented at senior secondary level in Srilankan Classrooms. The researcher randomly selected nine secondary schools from the Colombo district to represent the different school types such as: a National school, 1AB, 1C, and Rural/ Urban, Male/Female/ Mixed criteria. The sample was limited to secondary students of grades 10 (Senior Secondary), and teachers of these classes. Fifteen teachers of History and Civic subjects in the grade 10 were also selected as sample. In addition, Five ISA’s were selected from Colombo south educational division. Methodology of the study included the administration of a questionnaire for students as well as the teachers. Interviews were held with ISA of relevant subjects and teachers, to find out the procedures and processes adopted for implementation of Student Centred Education teaching and learning in the school system. The objectives of the interview were to triangulate the data obtained through self-administered questionnaire. Grade ten History and Civic Education classes were observed to examine how this concept could be implemented during the teaching learning process. The data was analysed using quantitative and qualitative methods. The major findings of the study were (1). Most of the students of National schools nurture a very optimistic attitude towards Student Centred Education,(2) Some teachers do not follow the activity method even if the suggested activities are given in the teachers guide, (3) Students prior needs are unheeded,(4) The concept is not given an important place in the curriculum,(5) Teachers of provincial council schools do not employ the Student Centred teaching techniques in the teaching learning process, (6) Many National school teachers implement a large variety of Student Centred Techniques although a few techniques are ignored. Based on the findings recommendations are made as to how the teachers, ISAs, Principals and students could develop their roles to achieve this concept.